2010
DOI: 10.1097/aap.0b013e3181df2527
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Popliteal Block Distal to Sciatic Nerve Bifurcation Shortens Onset Time

Abstract: Our data suggest that popliteal SNB distal to the bifurcation has a shorter onset time than SNB proximal to its bifurcation, and therefore, it may be a good option when a fast onset for a surgical block is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 17 publications
1
45
1
Order By: Relevance
“…However, these authors evaluated the block for a duration of 60 minutes. 3 In contrast, because of operating room constraints, we used a temporal cutoff of 30 minutes. For the sake of argument, even if all failures in our study (4 in the SUB group; 11 in the SEPI group) became successes in extremis at 60 minutes, a difference would still persist between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors evaluated the block for a duration of 60 minutes. 3 In contrast, because of operating room constraints, we used a temporal cutoff of 30 minutes. For the sake of argument, even if all failures in our study (4 in the SUB group; 11 in the SEPI group) became successes in extremis at 60 minutes, a difference would still persist between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Depending on where the needle tip is inserted and the spread of LA solution, significant differences in onset time and duration of sensory and motor blockades have been reported. [8][9][10][11][12][13] The recent literature highlights the importance of obtaining an extraneural concentric distribution of LA around the sciatic nerve 1,14,15 or an extraneural injection surrounding both tibial and peroneal nerves distal to the bifurcation. 12,13,16 In 2 studies, a proximal injection below the paraneural sheath seemed superior to an extraneural distal injection around both separate tibial and peroneal nerves.…”
mentioning
confidence: 99%
“…Buys et al [3] reported that the block performance time of ultrasound guided SNB with the lateral approach in the supine position, which was defined as the time elapsed from the insertion of the block needle until the completion of local anesthetic injection, was 2.9 ± 1.7 (mean ± SD) min. Prasad et al [5] reported that the block performance time of ultrasound guided SNB with the lateral approach in the prone position, which was defined as the time elapsed from ultrasound transducer preparation until the completion of anesthetic injection, was 9±3 (mean ± SD) min. In our study, the block performance time of SNB, which we defined as the time from insertion of the block needle until completion of injection of ropivacaine, was only 1.8 ± 0.5 min, and the block performance time for both SNB and FNB was 3.7 ± 0.8 min.…”
Section: Discussionmentioning
confidence: 99%
“…When the sciatic nerve (SN) is blocked with the lateral approach in the supine position, the lower limb must be sufficiently elevated to enable adequate space around the knee joint for transducer application [2,3]. When the SN is blocked in the prone position, patients require their position to be changed for additional FNB and/or surgery [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation